Learning Vocabulary in Another Language Arabic, English and Malay - Suhainim, Said (Universiti Malaysia Sarawak, UNIMAS, 2009)
This study was carried out with the aims of identifying the actual and perceived vocabulary learning strategies used by students taking Arabic classes in learning Arabic, English and Malay and specifically attempts to achieve these specific objectives:(1) to identify the various strategies of vocabulary learning used by students who are taking Arabic classes in acquiring Arabic, (2) to compare the difference in types of strategies used to learn 1st language and 2nd language, and (3) to identify the similarities and the differences between the perceived and the actual strategies used by Malay students in learning Arabic and English. In obtaining the data, questionnaires were administered among the students who are taking Arabic classes level 1 in UNIMAS and interview was conducted on three Arabic lecturers in Center of Language Studies (CLS) and also Arabic level 1 and 2 students. The total number of respondents involved in this is 62. Based on the findings of this study, there is a difference between the perceived and the actual strategies as learners might think that sometimes they use a particular vocabulary learning strategy not because it works, but because they think that they should be able to learn that way. Another finding is in relation with one of the vocabulary learning strategies that the learners reported they frequently used which is interaction with friends, classmates and their instructors. It can be concluded that interaction does play an important role in language learning. Besides, the use of bilingual dictionary is also one of the most frequently used strategies among the respondents. Another finding is that there is a slight difference in using vocabulary strategies when learning English, Arabic and Malay. Further studies shall be conducted in order to enrich the findings on this issue by involving a larger scale of respondents from all over Malaysia region. Besides, qualitative study shall be conducted for a clearer and deeper understanding towards the issue of language learning.